KOMPETENSI GURU PENDAMPING PAUD DALAM MEMENUHI STANDAR LAYANAN PAUD NON FORMAL DI KABUPATEN TASIKMALAYA - Aip Saripudin (AWLADY : Jurnal Pendidikan Anak, 2019)
Abstract Teachers should have gained the target of high quality are four competencies will be (1) competence of the personality (2) professional competency (3) competence of pedagogik and (4) social competence. Many strategys has been done by the government in order to realize the teachers of high quality of early childhood education, it which is through provide guidance on the formulation of teachers and education staff of early childhood education. This study used a qualitative methodology that was served a sort of descriptive set explorative. The place of the study is Kecamatan Cikatomas District Tasikmalaya .The technique of data collection through interviews, review of documentation, focus group discussions and questionnaires. The technique of processing data was undertaken through data collection, the reduction of the data, data presentation used to, and the withdrawal of a conclusion. Analysis techniques data using content analysis. The results of the study paper work showing that some aspects in the competence of a pedagogue is still classified as low, and it is requisite to the existence of the form of a strengthening it should also be noted a method of out of school in droves. The aspect of professional competency is still classified as low, can be seen from several aspects of the results of the review of documentation , interview and other of any economic indicators that is indicative of the teacher had not yet over matter of learning of early childhood education paud. Social competence also is still classified as low, can be seen from a number of aspects that is even social program has never been undertaken. This becomes an important issue attention and support the government in to increase the capacity of educator of early childhood education paud that is in kabupaten tasikmalaya especially for the institution of early childhood education paud non formal. Keyword: Competensi, pedagogy, professional, social, PAUD Standar AbstrakGuru berkualitas harus memiliki empat kompetensi yakni (1) Kompetensi Kepribadian (2) Kompetensi Profesional (3) Kompetensi Pedagogik dan (4) Kompetensi Sosial. Berbagai strategi telah dilakukan oleh pemerintah untuk mewujudkan guru PAUD yang berkualitas yakni melalui pembinaan pendidik dan tenaga kependidikan PAUD. Penelitian ini menggunakan metode kualitatif yang disajikan secara deskriptif  eksploratif. Tempat penelitian yakni lembaga PAUD non formal yang berada di Kecamatan Cikatomas Kabupaten Tasikmalaya. Teknik pengumpulan data melalui wawancara, telaah dokumen, focus group discussion (FGD) dan kuesioner. Teknik pengolahan data dilakukan melalui pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Teknik analisis data menggunakan teknik analisis isi (Contents Analisys) dan diperkuat dengan teknik prosentase. Hasil penelitian menunjukan bahwa beberapa aspek dalam kompetensi pedagogi masih tergolong rendah, sehingga perlu adanya penguatan secara metode dalam pembelajaran. Aspek kompetensi profesional masih tergolong rendah, terlihat dari beberapa aspek hasil telaah dokumen, wawancara serta angket yang menunjukan guru belum menguasai materi pembelajaran PAUD. Kompetensi sosial juga masih tergolong rendah, terlihat dari beberapa aspek sosial yang bahkan belum pernah dilakukan. Hal ini perlu perhatian dan dukungan pemerintah dalam meningkatkan kapasitas pendidik PAUD yang ada di kabupaten Tasikmalaya khususnya bagi lembaga PAUD non formal.Kata kunci: Kompetensi, pedagogi, professional, sosial, standar layanan PAUD